Recent trends in bagassosis in Japan. Issue 7 (July 1992) - Ueda, A; Aoyama, K; Ueda, T; Obama, K; Ueno, T; Hokama, S; Nomura, S
Abstract : The only workers presently exposed to bagasse dust in Japan are the employees of sugar refineries and lacquerware factories. A follow up study of six former cases of bagassosis from among the retired employees of a paper board factory, closed since 1973, showed that none of the subjects still had bagassosis. Examinations of 70 employees of a sugar refinery for allergic reactions also showed no case of bagassosis. Seven cases with suspicious shadows of bagassosis on chest radiographs and four cases with positive serum precipitin to stored bagasse were, however, found among those 70 subjects. The results show the disappearance of a past episode of bagassosis and the possibility of a new occurrence of bagassosis among the employees of sugar refineries and lacquerware factories in the near future in Japan.